Design and analysis of a combined floating photovoltaic system for electricity and hydrogen production - Temiz, Mert; Javani, Nader (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
The current study deals with a potential solution for the replacement of fossil fuel based energy resources with a sustainable solar energy resource. Electrical energy demand of a small community is investigated where a floating photovoltaic system and integrated hydrogen production unit are employed. Data are taken from Mumcular Dam located in Aegean Region of Turkey. PvSyst software is used for the simulation purposes. Furthermore, the obtained results are analyzed in the HOMER Pro Software. Photovoltaic (PV) electricity provides the required load and excess electricity to be used in the electrolyzer and to produce hydrogen. Saving lands by preventing their usage in conventional PV farms, saving the water due to reducing evaporation, and compensating the intermittent availability of solar energy are among the obtained results of the study for the considered scenario. Stored hydrogen is used to compensate the electric load through generating electricity by fuel cell. Floating PV (FPV) system decreases the water evaporation of water resources due to 3010 m(2) shading area. FPV and Hydrogen Systems provides %99.43 of the electricity demand without any grid connection or fossil fuel usage, where 60.30 MWh/year of 211.94 MWh/year produced electricity is consumed by electric load at $0.6124/kWh levelized cost of electricity (LCOE). (C) 2019 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Floating photovoltaic; Solar hydrogen; Fuel cell; Energy storage; ENERGY SYSTEM; PV; ELECTROLYZER; PERFORMANCE; OPTIMIZATION; TEMPERATURE; PLANTS; FUEL; Chemistry; Electrochemistry; Energy & Fuels